Retirement and home production: A regression discontinuity approach - Elena G. F. Stancanelli; Arthur van Soest (Institute for the Study of Labor (IZA), 2011)
Existing studies show that individuals who retire replace some private consumption by home production, but do not consider joint behaviour of couples. Here we analyze the causal effect of retirement of each partner on hours of home production of both partners in a couple. Our identification strategy exploits the earliest age retirement laws in France, enabling a fuzzy regression discontinuity approach. We find that own retirement significantly increases own hours of home production and the effect is larger for men than for women. Moreover, retirement of the female partner significantly reduces male hours of home production but not vice versa.
urn:nbn:de:101:1-201202284986
Keywords: J22; J26; J14; 330; time allocation; house work; couples; Altersgrenze; Haushaltsproduktion; Zeitverwendung; Frankreich